Magnetic, chemical and radionuclide studies of river sediments and their variation with different physiographic regions of Bharathapuzha River, southwestern India - Chaparro, Marcos A. E. (2015)
Bharathapuzha River is the second longest river in southwest India, where three physiographic regions show a distinctive spatial variation and their bed sediments can be considered environmental hosts for end-products generated by human activities and natural radionuclide components. Thus, the study of this river sediments in SW India is important not only because they are recorders of adverse human impacts (e.g., intense agricultural activities and urban pollution), but also because of their potential health hazards due to their common use as construction materials. Magnetic (e.g., magnetic susceptibility, anhysteretic remanent magnetisation and isothermal remanent magnetisation), radionuclide (226Ra, 232Th and 40K) and chemical (trace and major elements) measurements were carried out in bed sediment samples along 33 sites from the uppermost catchment downstream. Magnetic measurements show the dominance of ferrimagnetic minerals; their concentration ranges widely along the river and between regions, showing up to 7-fold higher values for concentration-dependent magnetic parameters, e.g., mean values of saturation of isothermal remanent magnetisation acquisition are 67.9 and 9.4  103 Am2 kg1 for highland and lowland regions, respectively. Multivariate statistical analyses show the existence of relationships between magnetic, radioactivity and chemical variables. In particular, magnetic concentrationdependent parameters are significantly correlated with radioactivity variables 40K and 226Ra (with concentrations about 20% higher than the worldwide mean values), as well as with some elements: Fe, Ca and P. Such analyses also show differences between physiographic regions where samples from the highland (and lowland) region are well grouped showing higher (lower) magnetic concentrations and lower (higher) coercivity minerals. The spatial variation of magnetic parameters along the river can be related to the influence of both natural sources and human activities, i.e. urbanisation and intense agricultural activities. In this sense, environmental magnetism data provide very useful tools to investigate adverse human activities occurring in the riverine environment.